Unfavorable prognostic value of CD24 expression in sections from primary and relapsed ovarian cancer tissue. Issue 2 (1st March 2006) - Surowiak, P.; Materna, V.; Kaplenko, I.; SpaczyŃSki, M.; Dietel, M.; Kristiansen, G.; Lage, H.; Zabel, M.
Abstract : Expression of CD24 represents a poorly recognized, unfavorable prognostic factor. Expression of the protein is supposed to facilitate extravasation of tumor cells. Our study aimed at examination of prognostic significance of CD24 estimation in samples obtained from primary surgeries (PS) and secondary cytoreductions (SCR) (after chemotherapy) in ovarian cancer patients. The analyses were performed on sections originating from 73 tumor samples. Immunohistochemical reactions were performed on paraffin sections of studied tumors, using monoclonal antibodies against CD24. Kaplan–Meier's analysis showed that a significantly shorter overall survival time and progression-free time was demonstrated to characterize cases with cytoplasmic membranous expression of CD24 (CD24c-m) ( P < 0.001). The calculations performed demonstrated also a significantly higher proportion of CD24c-m positive cases in sections from SCR as compared to that from PS ( P = 0.04) and in cases of progressive disease as compared to complete response at PS and SCR ( P = 0.002 and P = 0.05, respectively). Summing up, in this study, we have demonstrated a negative prognostic significance of a cytoplasmic membranous expression of CD24 in cases of ovarian cancer.